Análise global da influência da finura da cinza de casca de arroz como substituição parcial ao cimento Portland nas propriedades da argamassa de revestimento - Zaparte, Taiara Aparecida (2020)
The rice husk is used by some rice processing industries as fuel for their boilers, from this process originates the rice husk ash (CCA), which is mostlydeposited in open landfills, causing high environmental impacts. Research on this residue has already demonstrated its great potential for use as a Portland cement supplements, due to its main component, silica, in addition to the large surface area provided by its particles. But most studies focus on the control of the burning temperature of CA in order to produce a highly amorphous silica. Thus, there is still a gap in research that covers the effect of the fineness of CA obtained directly from industries, called residual. Therefore, this work aimed to investigate the influence that the reduction of residual CCA particles has on the properties of mortars in order to improve the pozzolanic activity of this pozzolan and develop a product with higher qualitythrough low energy expenditure. In addition, use it in cement materials in order to reduce the consumption of Portland cement, which generates impactsto the environment due to the large release of CO2in its production chain. To verify the influence on the mechanical, durability and microstructural properties, tests on the fresh and hardened state of the mortar were performed, as well as chemical and mineralogical analyses, in order to study its microstructure. From the data obtained from these tests, a global analysis of the mortars studied was performed, using tools from the decision-making process, in order to verify which mixture obtained the best performance. Four mixtures were produced, the reference one and others with residual unfilledand ground CCA for 2h and 3h, in a 15% cement substitution content. The mechanical tests were satisfactory for all mixtures with CCA, including the ash that did not go through the grinding process. The blendedwith ground CCA for 3h obtained the best results from the 28 days, both in the compressive strengthand in the flexural tensile strength. The water absorption and void index tests showed similar results among all mortars studied, with a slight advantage for mortars with ground CCA. The thermal and mineralogical analyses showed that the paste with unground CCA had a higher content of Ca(OH)2remaining when comparedwith the mixtures with ground CCA. SEM images indicated a denser formation of the microstructure of the mixtures with ground CCA comparedto the reference and unground CCA mixtures. With the overall analysis, it was concluded that the mixture with ground CCA for 3h achieved the best performance significantly, indicating that the reduction in the fineness of rice husk ash has great influence on pozzolanic activity by improving mechanical properties and durability, from a higher consumption of portlandite and physical effects such as filling voids and better internal arrangement of hydrated products.